Post-partum detention of insolvent women and their newborns in Lubumbashi, Democratic Republic of the Congo: a cross-sectional survey - Karen D Cowgill, PhD; Abel Ntambue, PhD (Elsevier, 2017)
Background: In the Democratic Republic of the Congo (DR Congo), maternal mortality is high, government financing for health care negligible, and 80% of people live in poverty. Women unable to pay hospital charges may be detained in hospital beyond the standard 3 days after an uncomplicated birth or 10 days after a caesarean. Here, we aimed to document policy and practice around detention of women in the maternity ward of a large government hospital in Lubumbashi, DR Congo. Methods: In a cross-sectional survey of post-partum women in the Jason Sendwe Hospital's maternity ward, we collected information on socioeconomic, demographic, and obstetric characteristics, and recorded the number of mother-infant pairs detained for non-payment of medical fees. We conducted semi-structured interviews with clinical staff and administrators about policy, and did a retrospective record review to identify the number of mother-infant pairs that had been detained for non-payment in 2014 and 2015. Findings: Of 85 women in the maternity ward and eligible for discharge between August 5 and September 15, 2016, 46 (54%) were detained for non-payment of medical fees. Median duration of detention was 5 days (range 1-30) and amounts owed were between US$8 and $611 (median $317). All the detained women in this study had received emergency care for delivery-related complications. To leave, four women went into debt, three sold belongings, and 14 were released when a politician paid their bills; 25 had not resolved their detention by study end on (September 15, 2016). From the retrospective record review, we identified 2446 deliveries at Sendwe hospital in 2014 and 2015; of these, 716 files included discharge data, and we retrospectively identified 108 cases of post-partum detention. From interviews with ten hospital clinical staff and administrators, we noted that detention of post-partum women and their infants for non-payment of hospital fees is accepted practice, and that hospital and staff depend on revenue from the maternity unit for hospital operating costs, including staff salaries. Interpretation: Cost recovery can increase out-of-pocket payments and limit access to care for health-care users. Dependence on user fees has also put health-care providers and facility administrators in a difficult situation, since money for their salaries and supplies must come out of revenues, which may be insufficient if users do not pay. We hope our findings about reasons for, and the frequency of, detention for non-payment of fees will support proposals for changes in policy and alternative models of health-care financing in DR Congo. Such changes would improve quality and access to care and reduce or eliminate the human rights violation of post-partum detention of women who cannot pay hospital fees. Funding: None.